2016
DOI: 10.1038/srep21800
|View full text |Cite
|
Sign up to set email alerts
|

A versatile strategy for rapid conditional genome engineering using loxP sites in a small synthetic intron in Plasmodium falciparum

Abstract: Conditional genome engineering in the human malaria pathogen Plasmodium falciparum remains highly challenging. Here we describe a strategy for facile and rapid functional analysis of genes using an approach based on the Cre/lox system and tailored for organisms with short and few introns. Our method allows the conditional, site-specific removal of genomic sequences of essential and non-essential genes by placing loxP sites into a short synthetic intron to produce a module (loxPint) can be placed anywhere in op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 23 publications
3
158
0
Order By: Relevance
“…To gain insights into this role we therefore adopted the DiCre conditional recombinase system recently adapted to P. falciparum (Collins et al, 2013) to examine the consequences of functional inactivation of RhopH3. For this, we used Cas9-mediated genome editing (Ghorbal et al, 2014) to introduce synthetic introns containing loxP sites (Jones et al, 2016) into the rhopH3 gene such that they flanked an internal region spanning exons 4–6, the region of the gene that shows the highest level of conservation across Plasmodium rhopH3 orthologs (Figure 1A, Figure 1—figure supplement 1). This genomic modification was made in the DiCre-expressing P. falciparum 1G5DC parasite clone (Collins et al, 2013) in order that excision of the floxed sequence could be induced by treatment of the transgenic parasites with rapamycin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insights into this role we therefore adopted the DiCre conditional recombinase system recently adapted to P. falciparum (Collins et al, 2013) to examine the consequences of functional inactivation of RhopH3. For this, we used Cas9-mediated genome editing (Ghorbal et al, 2014) to introduce synthetic introns containing loxP sites (Jones et al, 2016) into the rhopH3 gene such that they flanked an internal region spanning exons 4–6, the region of the gene that shows the highest level of conservation across Plasmodium rhopH3 orthologs (Figure 1A, Figure 1—figure supplement 1). This genomic modification was made in the DiCre-expressing P. falciparum 1G5DC parasite clone (Collins et al, 2013) in order that excision of the floxed sequence could be induced by treatment of the transgenic parasites with rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…The repair plasmid, called pESS_R3_E46_loxP (synthesised by GENEWIZ, South Plainfield, NJ) comprised synthetic heterologous loxP -containing SERA2 and sub2 introns (Jones et al, 2016) flanking a recodonized form of rhopH3 exons 4–6. The complete native sequences of exons 3 and 7 were included on either side of this central module to act as flanking regions for homology-directed repair.…”
Section: Methodsmentioning
confidence: 99%
“…We exploited a combination of recently developed Cas9 technology with conditional gene excision (3336) to obtain an inducible disruption of the gene in order to examine the essentiality of PFA0210c in P. falciparum . For this, we replaced the native PFA0210c open reading frame with a form interrupted by a loxP -containing intron (37). This was followed by 855 bp of a re-codonized PFA0210c -coding sequence plus a second loxP site immediately following the stop codon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While this however does not confirm that these two FIKKs are essential, the fitness cost to the parasite clearly indicates that they have important roles within the parasite, which is in line with our present conclusions. Another study (Jones et al, 2016) used a unique gene knock-out method and suggested that fikk10.1 loci may be dispensable. This method was also able to disrupt merozoite surface protein 1 (MSP1), a parasite protein expressed in merozoite-stage parasites and involved in invasion of RBCs, and previously believed to be essential for parasite survival (Drew et al, 2004), suggesting that this strategy could be used to study genes that cannot be targeted using The size of the proteins in amino acids (AA) and molecular weight in kDa is shown on the right.…”
Section: Discussionmentioning
confidence: 99%